Health systems in transition : learning from experience - McKee, Martin; Cain, Jennifer; Lessof, Suszy (Geneva, 2004)
"The period following the break-up of the Soviet Union has brought enormous political and socioeconomic change to the WHO European Region. The health sector has not been spared the effects of transition, and the countries emerging from the process have each engaged to varying degrees in health system reform. It is at last possible to reach some judgement about how this process has unfolded, to identify successes and failures, and to understand better the scale and nature of the remaining challenges. This book draws on the experience and lessons learned in the Region over the past ten years of transition in key health systems areas, such as health care financing, the restructuring of hospitals, public health and gains in health system quality."